THE EFFECTIVENESS OF DIGITAL MEDIA IN LEARNING ISLAMIC RELIGIOUS EDUCATION (PAI) IN THE ERA OF SOCIETY 5.0: STUDY OF THE INTEGRATION OF TECHNOLOGY AND RELIGIOUS VALUES - Darni Hafizah Almardiah; Andi Abd. Muis (Yayasan Haiah Nusratul Islam, 2025)
The Society 5.0 era marks a fundamental transformation in the education system, including Islamic Religious Education (IRE) learning. This study examines the effectiveness of digital media in IRE learning in the Society 5.0 era, focusing on the integration of modern technology and traditional religious values. Through a literature review and descriptive analysis approach, this study identifies the various digital media used in IRE, analyzes their effectiveness levels, and formulates strategies for optimizing learning. The research findings indicate that digital media such as e-learning platforms, Islamic education apps, immersive technology, social media, e-books, Islamic educational games, and Artificial Intelligence (AI) have proven effective in enhancing students' learning motivation. However, challenges arise in terms of integrating technology with traditional teaching methods and proficiency in using ICT. This study recommends PAI learning strategies that integrate modern technology with the reinforcement of Islamic religious principles to achieve holistic educational goals in the Society 5.0 era.